2012
DOI: 10.1164/rccm.201108-1503oc
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical and Environmental Determinants of Airway Transcriptional Profiles in Allergic Asthma

Abstract: Rationale: Gene expression profiling of airway epithelial and inflammatory cells can be used to identify genes involved in environmental asthma. Methods: Airway epithelia and inflammatory cells were obtained via bronchial brush and bronchoalveolar lavage (BAL) from 39 subjects comprising three phenotypic groups (nonatopic nonasthmatic, atopic nonasthmatic, and atopic asthmatic) 4 hours after instillation of LPS, house dust mite antigen, and saline in three distinct subsegmental bronchi. RNA transcript levels w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 30 publications
5
28
0
Order By: Relevance
“…Moreover, the magnitude of these allergic asthma-associated epigenetic signals is substantial when compared with other diseases(38, 39). These findings suggest that genes that have been previously reported to be differentially expressed in the airway epithelium of allergic asthmatics(1416) may be regulated by epigenetic mechanisms.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Moreover, the magnitude of these allergic asthma-associated epigenetic signals is substantial when compared with other diseases(38, 39). These findings suggest that genes that have been previously reported to be differentially expressed in the airway epithelium of allergic asthmatics(1416) may be regulated by epigenetic mechanisms.…”
Section: Discussionsupporting
confidence: 54%
“…Gene expression profiles of the allergic asthmatic airway(1416) and nasal(17) epithelia demonstrate that these cells are involved in an active biological process. Our findings demonstrate a clear relationship between DNA methylation and gene expression in the nasal epithelia of young allergic asthmatics using a stringent analytical pipeline to ensure that methylation changes we identified are not false positives due to influence of demographic factors or technical variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SPRY2 differentially regulates lymphoid and myeloid cell functions relevant to allergic asthma 32 . HLA-DQB2 is biologically relevant to immune responses and has previously associated with asthma 33 . ETV6-ABL gene rearrangement can result in chronic myeloid leukemia associated with eosinophilia 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide association studies in humans have identified several loci associated with asthma in multiple study populations (9)(10)(11)(12)(13)(14), and a genome-wide association study of allergic rhinitis also identified multiple loci, some of which overlap with asthma loci (e.g., LRRC32, HLA-G, and TSLP) (15). Several studies have also identified gene expression profiles that differentiate normal versus AAD in affected tissue (16)(17)(18)(19)(20)(21).…”
Section: Clinical Relevancementioning
confidence: 99%